Effect of Neo-Boost Pesticide on Mortality and Development of Different Life Stages of Two-Spotted Spider Mite, Tetranychus urticae - Bruinsma, Kristie; Salehipourshirazi, Golnaz; Zhurov, Vladimir; Dagher, Fadi; Grbic, Miodrag; Grbic, Vojislava (Frontiers in Agronomy, 2021)
The two-spotted spider mite, Tetranychus urticae, is a polyphagous agricultural pest that feeds on over a thousand plant species and more than 150 crops. Its status as an agricultural pest is exacerbated by its outstanding potential to evolve resistance to pesticides. The existence of multiresistant mite populations challenges mite management and creates a need for the development of pesticides with novel modes of action. In this study, we evaluated the acaricidal activity of Neo-Boost, a pesticide registered as a bactericide/fungicide/insecticide/miticide. Neo-Boost formulation contains three active ingredients: potassium silicate, sodium percarbonate and tetraacetylethylenediamine. In contact with water, the latter ingredients generate peroxyacetic acid, a potent contact bactericide and fungicide. Using the recommended field dose, we tested contact and residual effects of Neo-Boost on T. urticae egg, larval, and adult life stages. We found that Neo-Boost had no ovicidal effect. When tested on larvae, Neo-Boost caused 87% mortality over 48 hours post-treatment that was comparable to the positive control AGRI-mek SC (active ingredient abamectin), in addition to delaying larval developmental progression. On adult mites, Neo-Boost acted as a deterrent and caused 35% mortality (an intermediate effect compared to the positive control AGRI-mek SC). We also tested the proposed ability of Neo-Boost to induce a systemic response, however, it had no priming effect on treated tomato plants against mites. Of the individual Neo-Boost components tested, peroxyacetic acid and potassium silicate were not effective in any assay. However, sodium percarbonate, surfactant, and other non-listed components were sufficient for the full effectiveness of Neo-Boost formulations. Additionally, phytotoxicity of Neo-Boost was rare and minor when it occurred. Overall, despite the inefficiency of some compounds, the Neo-Boost formulation, either in its original or simplified formulation, may be useful for mite control on crops that are destined for fresh human consumption or medicinal use.